Experimental Study on Mechanical Integrity of Cement and EICP-Solidified Soil for Scour Protection of Pile Foundations - Feng Cao; Qilin Zhang; Wei Qin; Haoran Ouyang; Zhiyue Li; Yutao Peng; Guoliang Dai (Journal of Marine Science and Engineering, 2025)
Among the scour protection measures for pile foundations, the use of solidified mud has demonstrated effective protection against scour. However, research on the mechanical integrity of this protective measure is relatively scarce. Therefore, a series of experiments were performed on cement-solidified soil and Enzyme-Induced Carbonate Precipitation (ECIP) solidified soil to analyze fluidity, disintegration, and unconfined compressive strength, along with an analysis of influencing parameters. Test results show the following: for cement-solidified soil, fluidity decreases with higher cement content, while its disintegration rate decreases with more cement and its unconfined compressive strength increases with a longer curing time and higher cement content. For ECIP-solidified soil, fluidity decreases with higher soy powder concentration but increases with higher binder solution concentration. ECIP’s initial disintegration rate increases with binder concentration, but after 7 days curing, its disintegration rate decreases with both higher binder concentration and higher soy powder concentration. ECIP’s strength increases with higher soy powder concentration. Crucially, both types of solidified soil exhibit decreased unconfined compressive strength with higher initial water content. The research results can provide a reference for the construction of solidified soil in the field of scour protection.